The Effect of Profitability and Liquidity on Dividend Policy - Dwinanto Priyo Susetyo; Astrid Gloria Frankus; Deri Firmansyah (International Journal of Management and Business Intelligence, 2023)
This study examines the relationship between profitability projected by ROE and liquidity by CR to predict its effect on projected dividend policy with dividend payout ratio (DPR) in food and beverage sector manufacturing companies listed on the stock exchange market. Design and method of analysis, estimation of pandel data regression models with CEM, FEM and REM approaches using the EViews v.12 program. Approach model selection with Chow test, Hausman test, and LM test. The classical assumption test refers to the results of the best panel data regression model selected. The feasibility evaluation of the model was carried out by regression analysis of panel data, and analysis of the coefficient of determination, as well as the t test and F test, at a = 0.05. The results of the study, FEM as a regression model of selected panel data. Evaluation of the feasibility of the model, ROE and CR can predict changes in DPR behavior, although there is an inverse relationship of CR with DPR. The joint contribution of ROE and CR has a high ability to predict and influence the DPR. ROE has a significant negative effect on the DPR. CR has no influence on the DPR. Together, ROE and CR have proven to have a significant positive effect on the DPR.